Initial training for the digitalised work : example skilled workers supporting production in the automobile industry - Katzer, Olaf [Verfasser]; Kreher, Stefan [Verfasser]; Zinke, Gert [Verfasser] (My University, 2017)
"The digitalisation of work in the high-tech areas of the automobile industry and of the automobile supplier sector is a good example of the change in task and requirements profiles for skilled workers in engineering and plant construction. Within the scope of a pilot project, BIBB joined forces with the Volkswagen Academy to undertake a sample investigation of work tasks and activity profiles in the areas of operation, maintenance and repair of produc-tion systems. These were compared with existing training occupations and current training practice. After a brief description of the approach adopted, the article states the results which emerged and draws conclusions for pos-sible changes in the structuring of training within the framework of existing occupations. It concludes by illustrating how these changes are presently being implemented on a step-by-step basis." (author's abstract ; BIBB-Doku)
Ausbildungsgestaltung in der digitalisierten Arbeitswelt
Keywords: G 1.2.4.1 Produktion und Gewinnung; S 1.3 Berufliche Erstausbildung; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); Automobilindustrie; Betriebliche Berufsausbildung; Digitalisierung; Ausbildungsberuf; Tätigkeitsmerkmal; Fahrzeugtechnischer Beruf; Fahrzeug-Instandhalter; VOLKSWAGEN